Estimasi Biaya dan Evaluasi Kebutuhan Alat Muat dan Alat Angkut Terhadap Efisiensi Penambangan Batubara pada Tambang Terbuka PT. Allied Indo Coal Jaya, Sawahlunto - Nurul Anisa Ardianti; Heri Prabowo (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. Coal is an important energy source as a substitute for oil and gas fuels. Along with the increasing demand for coal, especially for steam power plants (PLTU) and for other industries, there has been an increase in coal production. An increase in the value of the dollar exchange rate against the value of rupiah reaching Rp. 14.091/$ USD throughout 2019 based on CNBC Indonesia and with falling coal prices in the world market calculated based on the average by ICI only 66,27 USD/ton, impacting coal mining companies in the world as well as PT. Allied Indo Coal Jaya. The importance of operating costs, owning costs and evaluating the need for loading and transporting equipment on production is certainly related to mining costs and the investment value to be incurred by the company and the production targets to be achieved by company. The relationship between production targets and the ability to produce equipment will determine the efficiency of operating costs and the cost of ownership and investment costs of equipment. With the NPV and IRR methods we can find out the feasibility of investing in loading and transporting equipment in relation to work efficiency and in the use of loading and transporting equipment used to meet these targets.Keywords: Effective Utilization, Operating cost, Owning cost, Net Present Value, Internal Rate Return